An anatomy of firms' political speech - Pablo Ottonello; Wenting Song; Sebastian Sotelo (Bank of Canada, 2024)
We study the distribution of political speech across U.S. firms. We develop a measure of political engagement based on firms' communications (earning calls, regulatory filings, and social media) by training a large language model to identify statements that contain political opinions. Using these data, we document five facts about firms' political engagement: (1) Political engagement is rare among firms; (2) Political engagement is concentrated among large firms; (3) Firms tend to specialize in specific topics and outlets; (4) Large firms tend to engage in a wider set of topics and outlets; (5) The 2020 surge in firms' political engagement was associated with an increase in the engagement of medium-sized firms and a change in the mix of political topics.
Keywords: D22; D63; G41; L11; L20; 330; Firm dynamics; Market structure and pricing; Recent economic and financialdevelopments